In Geolinguistics, Geographical Language Distribution: An Ethnographic Profile of the Website Ethnologue - rouina, abdelkarim (El Omda in Linguistics and Discourse Analysis, 2025)
This study seeks to describe the global ethnologue website, which specializes in statistics and graphic analysis of the linguistic and dialectical geographical distribution of the world's languages. Valuable and useful, molded in its geographical and graphic classification-based form, around the world's languages.